ANALISIS BAURAN PROMOSI TERHADAP PENJUALAN RUMAH: STUDI KASUS PADA PT. MINASA UPA PERSADA DI MAKASSAR - Bunyamin; Sultan Iskandar (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2021)
The research aims to find the influence of promotion mix on home sales at PT.Minasa Upa Persada Makassar. The method of collecting data were observation,interview and documentation. The research used total sampling that is all employesof PT. Minasa Upa Persada consists of 48 participants. The analysis method useddescriptive and multiple linear regressions. The hypotesis test used portal test withtest count and f test count, using SPSS 22.0, significant limit (0,05) the result showsthat advertising variable (X1), personal selling (X2), publicity (X3), and salespromotion (X4), portially has a positive and significat effect on home sales at PT.Minasa Upa Persada Makassar where the t-count > t-table (6,724 > 2,38)